Acute Disseminated Encephalomyelitis following Vaccination against Hepatitis B in a Child: A Case Report and Literature Review - Jun-liang Yuan; Shuang-kun Wang; Xiao-juan Guo; Wen-li Hu (Case Reports in Neurological Medicine)
Acute disseminated encephalomyelitis (ADEM) is an inflammatory demyelinating disease of the central nervous system, which has been associated with several vaccines such as rabies, diphtheria-tetanus-polio, smallpox, measles, mumps, rubella, Japanese B encephalitis, pertussis, influenza, and the Hog vaccine. Here, we presented a case of 12-year-old child who suffered from ADEM three weeks after hepatitis B vaccination. He was admitted to our hospital with symptoms of weakness of limbs, high fever, and alteration of consciousness. Some abnormalities were also found in CSF. Treatment with high-dose corticosteroids and intravenous immunoglobulin had significant effect, with marked improvement of the clinical symptoms and the results of CSF. The findings of MRI also detected some abnormal lesions located in both brain and spinal cord. The clinical features, the findings of CSF and MRI, and therapeutic effect may contribute to such diagnosis of ADEM.